Ferric Iron in CaTiO3 Perovskite as an Oxygen Barometer for Kimberlite Magmas II: Applications - Canil, Dante; Bellis, Anthony J. (Journal of Petrology, 2007)
We apply an oxygen barometer based on the Fe content of CaTiO 3 perovskite to estimate the oxygen fugacity ( f O 2 ) during the crystallization and emplacement of kimberlites in different eruptive phases of a single pipe, or between different pipes, clusters or provinces. Mineral chemical data for perovskite were compiled from the literature and obtained in our detailed study of perovskites from 11 kimberlites at Somerset Island and Lac de Gras, Canada. Perovskite compositions in kimberlites record a range in f O 2 of many orders of magnitude from NNO−5 to NNO+6 [where log f O 2 is given relative to the nickel–nickel oxide (NNO) buffer]. The range of f O 2 recorded by different parageneses of perovskite within a single pipe can vary up to three orders of magnitude with trends toward both oxidation and reduction during crystallization. Kimberlites record some of the greatest ranges, and the highest known f O 2 conditions for any terrestrial magma. This is attributed to the presence of deep and oxidized source regions and the variable interplay of ferric–ferrous vs carbon–fluid equilibria during ascent of kimberlite magmas. Three kimberlite pipes from the Lac de Gras field show that higher f O 2 values correlate with higher proportions of more resorbed diamonds, suggesting that this variable has a measurable effect on the physical properties of diamonds in a pipe.